(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
Freight forwarding services play a critical role in coordinating multi-modal shipments, managing logistics documentation, and ensuring time-sensitive delivery of perishable commodities. This study analyzes the export handling procedures for perishable fish commodities shipped via air freight at PT XYZ, a specialized freight forwarder operating near Soekarno-Hatta International Airport. Employing a qualitative descriptive method with a single case study design, data were collected through in-depth interviews with two supervisors and three operational staff, direct observation, and documentation review, validated through source and method triangulation. Findings reveal a structured 13-stage export procedure from order receipt to aircraft build-up that must be completed within a 4–6 hour closing-time window. Five operational constraints were identified: (1) delayed commodity information from exporters; (2) human error in document input; (3) external system failures (Badan Karantina Ikan and INSW); (4) cargo space limitations on commercial aircraft, identified as the most dominant constraint based on interview data; and (5) destination-country regulatory complexity. Applying Fishbone Analysis, root causes were traced to five dimensions human, method, machine, material, and environment and targeted strategic recommendations were formulated for each. This study contributes an empirically grounded procedural and analytical framework for perishable fish export logistics, offering practical implications for freight forwarders, airline cargo managers, and export policy stakeholders in Indonesia.